Overestimation of carotid stenosis on CTA – Real world experience. (March 2021) - Horev, Anat; Honig, Asaf; Cohen, Jose E.; Goldbart, Adi; Dizitzer, Yotam; Star, Michael; Gomori, John M.; Zlotnik, Yair; Ifergane, Gal; Borodetsky, Vladimir; Shelef, Ilan; Leker, Ronen R.
Highlights: Consecutive patients with a symptomatic carotid stenosis had a routine diagnostic DSA. Only 70/90 patients with significant stenosis on CTA, were found to have a significant stenosis on DSA. Severe plaque calcification was significantly more common in the false-positive group. In patients with 50–70% CTA reported stenosis positive predicted value was poor (PPV – 0.29) (p < 0.001). Abstract: Background: Symptomatic carotid stenosis is responsible for 10% of all strokes. Currently, CT angiography (CTA) is the main diagnostic tool for carotid stenosis. It is frequently the only diagnostic test preceding recommendations for carotid angioplasty and stenting (CAS) or carotid endarterectomy (CEA). However, the specificity of CTA, especially in patients with 50–70% stenosis, was previously reported to be relatively low. Most studies testing the diagnostic accuracy of CTA were published more than a decade ago. Therefore, we aimed to test the diagnostic accuracy of CTA, performed with current available technology, compared with digital subtraction angiography (DSA) in patients with carotid stenosis. This study aims to characterize patients who were candidates for CAS/CEA based on CTA, but may not require it based on DSA. Methods: Consecutive candidates for carotid interventions (CAS or CEA) following CTA were identified from prospectively maintained stroke center registries at two large academic centers. As part of our institutional practice all patients had a routine pre-procedural diagnostic DSA. In each patient, degree of carotid stenosis was compared between CTA and DSA. Patients with concordant degree of stenosis on DSA and CTA (true positive group) were compared to patients with a discordant degree of stenosis with less than 50% on DSA (false positive group). Results: Out of 90 patients with significant stenosis on CTA, only 70 (78%) were found to have a significant stenosis on DSA. Severe plaque calcification was significantly more common in the false-positive group. In those patients whose CTA reported stenosis of ≥90%, we found a strong agreement between CTA and DSA (positive predictive value [PPV] – 0.9) for a significant stenosis (≥50%). Conversely, the correlation between CTA and DSA in patients with CTA reported 50–70% stenosis was poor (PPV – 0.29) (p < 0.001). Conclusions: Our results suggest that despite ongoing radiological progress, the specificity of CTA in accurately assessing carotid stenosis remains relatively low in patients with both moderate stenosis and heavily calcified plaques. Consequently, patients could possibly be referred for unnecessary CEA surgery and may become exposed to associated potential complications.